Inverse functions

  1. how do i find
    f(x)^-1 of y=4x+9/2x-3
    the answer in the back of the text book is

    f(x)^-1=3x+9/2x-4
     
  2. jcsd
  3. Show your attempt at a solution, or pay me 1 dollar for doing your homework for you (your choice).
     
  4. 2x=4x+9/y + 3y/y
    2x=4x+9+3y/y
    How do i move 4x to the other side?
     
  5. is 9/2x in your original post 9/(2x)? Just want to check.
     
  6. Heres the full working out:
    y(2x-3)=4x+9
    2x-3=4x+9/y
    2x=4x+9/y + 3
    2x=4x+9/y + 3y/y
     
  7. You gotta learn to put brackets in your eqns. There's no way anyone could have understood your original problem without the brackets.

    y(2x-3)=4x+9
    x(2y-4)-3y=9
    x=(9+3y)/(2y-4)
     
  8. Sorry to bother u again but how
    do u get from
    y(2x-3)=4x+9 to
    x(2y-4)-3y=9
     
  9. expand and collect terms in x

    y(2x-3)=4x+9
    ->
    y2x-3y=4x+9
    ->
    x(2y)-3y=x(4)+9
    ->
    x(2y-4)-3y=9
     
Know someone interested in this topic? Share this thead via email, Google+, Twitter, or Facebook

Have something to add?